Aproximación al pintor dieciochesco Diego Gutiérrez - Calvo Ruata, José Ignacio (Artigrama, 2006)
Diego Gutiérrez Fita, nacido en Barbastro, desarrolló su principal actividad en Aragón durante el último tercio del siglo XVIII. Pintor poco conocido, se documenta ahora su ingreso como académico supernumerario de San Carlos (1778) y un pleito que se le puso con motivo de haber pintado en el santuario de la Virgen del Pueyo de Barbastro (1786). Se estudian varias obras, documentadas o atribuidas, existentes en Zaragoza (iglesia de la Santa Cruz), Tarazona (catedral), Barbastro (santuario del Pueyo y palacio episcopal) y Abay (lugar de Jaca)Diego Gutiérrez Fita was born in Barbastro. His main activity was developed in Aragón during the last third of the Eighteenth century. Not much known, it’s now documented his admission as a supernumerary member of the Royal Academy of San Carlos (1778). It’s also documented a lawsuit brought against him because a painting he made in the Virgen del Pueyo’s shrine of Barbastro (1786). Several works are studied, whether documented or attributed, existing in Zaragoza (Santa Cruz church), Tarazona (cathedral), Barbastro (Pueyo’s shrine and bishop’s palace) and Abay (place of Jaca)..